2009
DOI: 10.1128/aem.01928-09
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Novel Microcystin-Degrading Bacteria

Abstract: Of 31 freshwater bacterial isolates screened using the Biolog MT2 assay to determine their metabolism of the microcystin LR, 10 were positive. Phylogenetic analysis (16S rRNA) identified them as Arthrobacter spp., Brevibacterium sp., and Rhodococcus sp. This is the first report of microcystin degraders that do not belong to the Proteobacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(137 citation statements)
references
References 20 publications
5
132
0
Order By: Relevance
“…They observed a decrease in mlrA gene concentration during the degradation experiments, from 3.2 × 10 6 copies/L initially to 3.9 × 10 5 copies/L at day 7, which is similar to our observation of a decrease in mlrA gene concentrations in the degradation experiments ( Figure 7). The decrease in mlrA gene concentrations observed by Li et al [66] and in the current study might be due to the presence of bacteria with other degradation genes involved in the MCs' degradation process [33,38]. In addition, there was no statistically significant difference (p = 0.290) in mlrA gene evolution with or without the cyanobacteria enrichment, with a normal distribution for p = 0.49 and p = 0.21, respectively with and without the enrichment in M. aeruginosa.…”
Section: Biomolecular Aspect Of Mc-lr Degradation In Hlpl Watersupporting
confidence: 51%
“…They observed a decrease in mlrA gene concentration during the degradation experiments, from 3.2 × 10 6 copies/L initially to 3.9 × 10 5 copies/L at day 7, which is similar to our observation of a decrease in mlrA gene concentrations in the degradation experiments ( Figure 7). The decrease in mlrA gene concentrations observed by Li et al [66] and in the current study might be due to the presence of bacteria with other degradation genes involved in the MCs' degradation process [33,38]. In addition, there was no statistically significant difference (p = 0.290) in mlrA gene evolution with or without the cyanobacteria enrichment, with a normal distribution for p = 0.49 and p = 0.21, respectively with and without the enrichment in M. aeruginosa.…”
Section: Biomolecular Aspect Of Mc-lr Degradation In Hlpl Watersupporting
confidence: 51%
“…In addition, a number of research groups had performed microorganism isolation with MCs served as sole carbon and nitrogen source (Valeria et al, 2006;Zhang et al, 2010) and they believed other substrates may be preferentially degraded, leading to depression of the target substrate (Markiewicz et al, 2011), while some other reports found that utilization of the target substrate were not prevented by additional carbon source. This was supported by Edwards et al (2008) who demonstrated the utilization of MCs by bacteria in river and subsequently enriched them by direct addition of MCs in the river water (Manage et al, 2009). In our studies, the TOC and TN concentrations of the media ranged from 1.08 to 5.82 mg L −1 , which were significantly higher than some isolation process (Zhang et al, 2010), resulted in delay but not inhibition of bacteria growth.…”
Section: Influence Of Nutrient Condition On Bacteria Isolationmentioning
confidence: 86%
“…Microcystins possess stable chemical structure in water and thus different water treatment approaches including filtration, coagulation and flocculation are found inefficient in decreasing the concentration of these toxins in the fresh water reservoirs (Manage et al, 2009). Thus, the risk associated with their toxicity remains very high.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of toxic cyanobacterial blooms in numerous natural freshwater bodies and possible use of such water in human consumption initiated work on biodegradation of cyanotoxins (Lam et al, 1995). Diversity of microbial species with ability of microcystin degradation and nodularin with tentative recognizance of novel degradation intermediates were reported (Manage et al, 2009). It was shown that MCYST can undergo biodegradation by certain aquatic bacteria like strains of the genus Sphingomonas (Saitou et al, 2003;Valeria et al, 2006) owing to the existance of an enzymatic degradation mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation